Water Harvesting and Moisture Conservation Practices for Dry Farming of Maize and Mustard in U.P. - Bhan, Suraj; Singh, S R (Annals of Arid Zone, 2016)
A field investigation was conducted during 1973-74 and 1974- 75 at Kanpur to explore the feasibility (If double cropping of maize mustard by inter-row water harvesting and moisture conservation practices under dryland conditions of Central Uttar Pradesh. The results showed that inter-row water harvesting (ridging and furrowing), paddy straw mulch combined with chemical weed control made the maize 'T41 '-mustard 'KB2' rotation successful and profitable under rainfed conditions. Ridging and furrowing increased the yield of maize and mustard and brought about an additional profit of Rs. 2g5.60/ha over the conventional method (flat sowing). Similarly, paddy straw mulch (2 t/ha) combined with weedicide application (Simazine @ I kg a.i./ha in maize and Tok E-25 @ 2 kg. a.i./ha in mustard) increased the yield of maize by S.44 q/ha and mustard by 8.70 q/ha and resulted in an additional profit of Rs. 1758fha over control. Polyethylene mulch was also found effective in increasing the yield of maize and mustard but owing to the high cost its use was not found economical.